Skilling and Its Histories: Labour Market, Technical Knowledge and the Making of Skilled Workers in Colonial India (1880–1910). (December 2018) - Kumar, Arun
Written in the backdrop of the emerging official discourse around occupational skill training in contemporary India, this article returns to the past to explain how the meanings of skill and skill training were produced through the interaction of the colonial education system and industrial actors in modern India. Using archival records, it studies the history of the Lucknow Industrial School—one of the earliest government institutes to skill Indians in various industrial trades and for the local railway workshop. The article argues that industrial training institutions, while crucial in defining and legitimizing a discourse of skill and efficiency based on the scientific and technical knowledge of workers, were subjected to the competing political and training discourses of the shop floor, financial unwillingness of the British empire to create a large infrastructure of industrial and technical education for the colony, local caste politics and aspirations of students. All these forces shaped the nature of skill transference and produced unintended results which strained the relationship between the training institute and industries. Similar conflicts and issues surround the contemporary skill programme. A historical study of skill development during the colonial era allows a better understanding of the prospect and perils of the present-day Skill India Mission.